The Goofer Pitch - Heuman, William (New York Dodd, Mead and Company, 1969)
The old pitch against prejudice. Andy, doubling as team captain and coach since their regular coach went back to college, decides rich Steve Randolph can join the Bantams. Skeeter Gonzales, stereotyped poor, here Puerto Rican, is the better hurler but Steve masters the Goofer Pitch, a floater that catches other teams off guard. With Andy spending time at Steves mansion, Skeeter is slighted and the rest of the team grows resentful. But then Steves monkey, the team mascot, gets up a tree and only Skeeters Spanish can coax him down. Thats supposed to reunite them but kids will see right through it.
Keywords: Children Literature